ELECTROCARDIOGRAM OF PIGS (Sus scrofa) ANESTHETIZED WITH A COMBINATION OF KETAMINE-MEDETOMIDINE AND KETAMINE-ACEPROMAZINE - Safitri, Jessica Anggun; Gunanti, Gunanti; Noviana, Deni; Widhyari, Sus Derthi (Universitas Syiah Kuala, 2020)
This study aims to evaluate and compare the effects of the combination of ketamine-medetomidine and ketamine-acepromazine anesthesia on pig electrocardiogram (ECG) images. The study was conducted to see the ECG Leads II in six pigs which were divided into two groups. Group I (K1) was given a combination of ketamine (10 mg/kg BW) and medetomidine (0.08 mg/kg BW), while Group II (K2) was given a combination of ketamine (22 mg/kg BW) and acepromazine (1.1 mg/kg BW) intramuscularly. ECG recording was performed after the pigs were anesthetized at the surgical stage by attaching the recording electrodes to the front wall of the chest, front left and right ankles, and back right and left back ankles. The ECG recording used 1 voltage (1 cm = 1mV) with a speed of 25 mm/sec. The parameters observed were heart rate frequency, heart rhythm, P duration, P amplitude, PR interval, R amplitude, QRS interval, QT interval, ST segment, T wave, and Mean Electrical Axis (MEA). Data obtained from this study were analyzed by T-test. The results showed that K1 had an average heart rate of 100 x/minute, regular heart rhythm, P duration of 0.07 sec, P amplitude of 0.27 mV, PR interval of 0.17 sec, R amplitude of 0.75 mV, QRS interval of 0.05 sec, QT interval of 0.20 sec, ST segment of 0.17sec, T wave of 0.17 mV, and MEA of 83.60; meanwhile, K2 had an average heart rate of 122 x/minute, regular heart rhythm, P duration of 0.06 mm/sec, P amplitude of 0.23 mV, PR interval of 0.14 sec, R amplitude of 0.80 mV, QRS interval of 0.04 sec, QT interval of 0.16 sec, ST segment of 0.14 sec, T wave of 0.12 mV, and MEA of 68.60. The ketamine-medetomidine combination produced good quality of anesthetics for the cardiovascular system.